Study of Copper Metallodrugs as Potential Inhibitor of Cancer via Molecular Docking and DFT - H R, Gopala Krishna Murthy; H.D., Revanasiddappa; B, Ajay Kumar; M, Prema; M, Mahendra; H, Keshav Kumar; BC, Vasantha Kumar; C, Sanjeevrayappa (Orbital: The Electronic Journal of Chemistry, 2025)
Cancer remains a leading cause of mortality worldwide, demanding the development of novel therapeutic strategies. Recent advances in molecular biology and pharmacology have facilitated the discovery of new agents with potential anti-cancer activity. This study aims to elucidate the mechanisms underlying the anti-cancer effects of several newly identified compounds and assess their efficacy in preclinical models. As per literature, several compounds were screened for anti-cancer activity using a combination of in-vitro and in-vivo assays. In our research the in-silico analysis approach is used to explore the interactions between prepared compounds and Cyclin-Dependent Kinase 2 (CDK2), which is a crucial protein involved in cell cycle regulation and apoptosis. Immunohistochemistry will identify pathways involved in the compounds’ anti-cancer effects. The study identified several compounds with a significant anti-cancer activity, demonstrating a dose-dependent inhibition of cancer cell proliferation and induction of apoptosis. Notably, our compounds exhibited the highest potency, leading to a substantial reduction in tumour growth in xenograft models.